2010
DOI: 10.4028/www.scientific.net/ast.63.352
|View full text |Cite
|
Sign up to set email alerts
|

Defect Crystal Structure of Low Temperature Modifications of Li<sub>2</sub>MO<sub>3</sub> (M=Ti, Sn) and Related Hydroxides

Abstract: Crystal structures of Li2MO3 (M=Sn, Ti) and TiO(OH)2 have been studied in detail and refined using X-ray powder diffraction data. All compounds posses a high concentration of defects in the structure. The crystal structures of the Li2MO3 salts obtained at 700°C reveal stacking faults of LiM2 metal layers, which leads to the appearance of short-range order in three possible space groups: C2/c, C2/m, P3112. The possibility to stabilize this imperfect state increases the mobility of the Li+ ions in the Li2TiO3 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…However, if the crystal structure of the monoclinic modification obtained at temperatures above 1270 K is described in detail in [9,18], then for LТ phases until recently there were only some indications of their belonging to layered compounds based on the NaCl structure type [16]. In [19,20] we refined the crystal structure of the LT phase of monoclinic Li 2 TiO 3 by analyzing X-ray diffraction and electron diffraction patterns. It is shown that the LT phase of Li 2 TiO 3 is less ordered relative to the HT phase due to a violation of LiTi 2 O 6 layer packing, which results in the formation of three types of local symmetry C2/c, C2/m, and P3 1 21.…”
Section: S112mentioning
confidence: 99%
“…However, if the crystal structure of the monoclinic modification obtained at temperatures above 1270 K is described in detail in [9,18], then for LТ phases until recently there were only some indications of their belonging to layered compounds based on the NaCl structure type [16]. In [19,20] we refined the crystal structure of the LT phase of monoclinic Li 2 TiO 3 by analyzing X-ray diffraction and electron diffraction patterns. It is shown that the LT phase of Li 2 TiO 3 is less ordered relative to the HT phase due to a violation of LiTi 2 O 6 layer packing, which results in the formation of three types of local symmetry C2/c, C2/m, and P3 1 21.…”
Section: S112mentioning
confidence: 99%
“…A more complex approach has to be proposed in order to control the refinement process better, probably the lamellar shape and the small size of the particles have to be included, as well as possible structural defects, as demonstrated for the Li 2 TiO 3 compound. 23,31,32 Similarity in positions and intensity of the lines on the Raman spectra of the Li 2 MO 3 (M = Zr, Hf ) salts indicates that these compounds are isostructural (Fig. 4).…”
Section: Quantum-chemical Calculationsmentioning
confidence: 88%
“…It possesses a lot of disorder in the structure, partly preserved from the structure of the Li 2 TiO 3 precursor. 23,31,32 The main goal of this study is to solve the crystal structure of the new MO(OH) 2 (M = Zr, Hf ) compounds using crystallographic information about the related lithium salt, obtained by a citrate synthesis. Our preliminary study and results published by Chai et al 33 show that oxyhydroxides of the 4 th group of the periodic table have a high sorption affinity for polyvalent ions, including radioactive ions (Ag, Tl, As, Te, Sr, Th, U etc.).…”
Section: Introductionmentioning
confidence: 99%
“…However, in our recent studies it has been shown that the use of an ion exchange reaction with Li 2 HfO 3 as a precursor allows to synthesize a crystalline HfO(OH) 2 compound as an individual phase (Baklanova et al, 2011). In the same way, other oxyhydroxides from the IVB group of the periodic table (TiO(OH) 2 and ZrO(OH) 2 ) have been synthesized and their physicochemical properties have been studied recently (Baklanova et al, 2011;Orera et al, 2005;Denisova et al, 2006;Yawata, 2006;Tarakina et al, 2010a;Tarakina et al, 2010b;Tarakina et al, 2011). However, only the crystal structure of TiO(OH) 2 has been described (Tarakina et al, 2010a;Tarakina et al, 2010b;Tarakina et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In the same way, other oxyhydroxides from the IVB group of the periodic table (TiO(OH) 2 and ZrO(OH) 2 ) have been synthesized and their physicochemical properties have been studied recently (Baklanova et al, 2011;Orera et al, 2005;Denisova et al, 2006;Yawata, 2006;Tarakina et al, 2010a;Tarakina et al, 2010b;Tarakina et al, 2011). However, only the crystal structure of TiO(OH) 2 has been described (Tarakina et al, 2010a;Tarakina et al, 2010b;Tarakina et al, 2011). It has been shown that titanium oxyhydroxide has a layered structure closely related to the structure of the low-temperature modification of the Li 2 TiO 3 salt; elements of disorder characteristic of the structure of the precursor are preserved in the structure of the oxyhydroxide as well.…”
Section: Introductionmentioning
confidence: 99%